2013
DOI: 10.1177/1355819613498380
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the proximity of patients’ nearest alternative hospital on their intention to search for information on hospital quality

Abstract: As fewer older, less educated patients would search for information to guide their choice, they might not opt for the best hospital. Additionally, the need for providers to compete for the patronage of these patients might be lessened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…This finding is consistent with international research in general patient groups (Victoor, Delnoij, Friele, & Rademakers, 2014) and cancer populations (Nostedt et al, 2014), and suggests that choice policies or guidelines currently have little impact on patients experiences of choosing a treating clinician or the location of their treatment. We found that most patients perceive little choice, regardless of cancer diagnosis or geography.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is consistent with international research in general patient groups (Victoor, Delnoij, Friele, & Rademakers, 2014) and cancer populations (Nostedt et al, 2014), and suggests that choice policies or guidelines currently have little impact on patients experiences of choosing a treating clinician or the location of their treatment. We found that most patients perceive little choice, regardless of cancer diagnosis or geography.…”
Section: Discussionsupporting
confidence: 83%
“…We found that most patients perceive little choice, regardless of cancer diagnosis or geography. This finding is consistent with international research in general patient groups (Victoor, Delnoij, Friele, & Rademakers, 2014) and cancer populations (Nostedt et al, 2014), and suggests that choice policies or guidelines currently have little impact on patients experiences of choosing a treating clinician or the location of their treatment. A lack of knowledge about cancer and healthcare providers, perceived urgency to act, perceptions about choice in the public health system and access issues acted as barriers to patient involvement in decisions.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…To judge the risk of bias (RoB) in the included studies, we referred to the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) publication on assessing certainty of evidence in the importance of outcomes and patients' preferences [12]. Domains in which the RoB should be assessed are: [1] selection of participants into the study, [2] completeness of data, [3] measurement instrument and [4] data analysis. We omitted the second domain (completeness of data) because in the identified studies, the no-response rate and the loss to follow-up were not involved.…”
Section: Risk Of Bias Of Individual Studiesmentioning
confidence: 99%
“…Younger age, higher education and willingness to travel in general are factors associated with more tolerance toward greater distances to a hospital. Some studies indicate that the distance to a hospital is even more important than medical outcomes [1][2][3]. Besides surgical reputation and surgical competency, hospital reputation and distance to the hospital are the primarily important attributes by which patients choose their surgeon [4].…”
Section: Introductionmentioning
confidence: 99%